Need Analysis for Developing an SDG 15 (Life on Land) Big Book to Support Preschoolers’ English Learning through Shared Reading - Ni Putu Eka Indah Tiari; Putu Kerti Nitiasih; Ni Wayan Monik Rismadewi (Abdi Cendekia : Jurnal Pengabdian Masyarakat, 2026)
This study aims to analyze the need for developing a Big Book based on Sustainable Development Goal (SDG) 15 (Life on Land) to support English learning for preschool children through shared reading activities at TK Lab Undiksha. This study was conducted as a preliminary stage in the development of learning media that integrates environmental awareness with early English learning. A qualitative descriptive design was used to identify learning needs, classroom conditions, student characteristics, and teacher’s expectations regarding the use of Big Books in English instruction. The study participants included teacher and preschool students at TK Lab Undiksha. Data were collected through classroom observation and interview. The findings indicate that early childhood learners demonstrate a high level of interest in visual and interactive learning materials, particularly those featuring colorful illustrations, repetitive language patterns, and simple vocabulary. However, current English learning materials remain limited in their integration of environmental education themes, specifically SDG 15 (Life on Land). Teacher also expressed a need for engaging, age-appropriate learning media that can enhance students’ vocabulary mastery, participation, and reading engagement during shared reading activities. This study concludes that the development of an SDG 15-based Big Book holds great potential to support English learning for preschool children while fostering environmental awareness through meaningful and interactive shared reading practices.